ANALYSIS OF THE STUDENTS’ ANXIETY IN SPEAKING ENGLISH - TARIGAN, SURYA SETIADI (Academic Journal of Educational Sciences, 2022)
The aim of the study is to know the students’ anxiety in speaking English at Kupang State Polytechnic. The population of this study is the first semester of company management major of Kupang State Polytechnic in 2022-2023 academic years and the sample are thirty students of class 1B. The sample is taken by random technique. This study is conducted by using descriptive qualitative research design of which data are taken through interviewing sheet. The most dominant anxieties of the students found in speaking English were grammar and pronounciation which have same percentage 46.7 % and followed the Peer were 6.6 %. Especially, the language was not found as the factor that caused the students’ anxiety in speaking English because English is not a strange language in the polytechnic level and it was an international language which must be learnt by all people in the world especially the students. While in the internal anxiety was dominated in lacking the confidence 73.3 % and fear 26.7%. And the ways of students in overcoming the anxiety in speaking English was through having good preparation, positive thinking, relax, and resigning. Making friends was not founded in this study.